Perbedaan status gizi, kesegaran jasmani, dan kualitas hidup anak sekolah di pedesaan dan perkotaan - Maria Mexitalia; Hendriani Sellina; Mohammad Syarofil Anam; Aya Yoshimura; Taro Yamauchi; Nurkukuh Nurkukuh; Bambang Hariyana (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2012)
Background: The differences in geographic, sosioeconomic and lifestyle between children in rural and urban areas infl uence their nutritional status. The urban children tended to be less active. The evidence suggested that physical activity improves cardiorespiratory fi tness and mental health in young people but study that compare those indicators among rural and urban children was scarce.Objective: To compare the nutritional status, physical fi tness, and quality of life between elementary school children in rural and urban areas.Method: A cross-sectional study was conducted at Semarang (urban) and Mlonggo (rural) Central Java in 2009. Inclusion criteria was school children aged 9-11 years and had no physical disability. Body composition was measured by Bioelectrical Impedance Analysis, physical activity by Global Physical Activity Questionnaire (GPAQ), physical fi tness by 20-m shuttle run test and quality of life by Pediatrics Quality of Life Questionnaire (PedQoL 4.0). The differences between nutritional status and physical activity were assessed by Chi Square test, while the differences between physical fi tness and quality of life were tested by independent t test (p<0.05).Result: One hundred sixty-two subjects were enrolled in the study (Semarang 82 students; 36 boys, 46 girls and Mlonggo 80 students; 40 boys, 40 girls). Body mass index (18.97 vs 15.16 kg/m2) and body fat (26.03% vs 18.03%) of urban children were higher than that of the rural’s (p<0.001). Children in rural area were signifi cantly more active, have higher physical fi tness level (VO2 max 28.54±1.79 ml/kg/min vs 21.57+1.79 ml/kg/min) (p<0.01), and have higher score in quality of life (2243 + 295,8) compared to the children from urban area (2133 + 369.4) (p<0.05). Conclusion: Rural school children have lower nutritional status than urban children, but they are more active and have higher physical fi tness level. They also have better quality of life.